Prevalence of subclinical hypothyroidism in North-Indian pregnant women - Goel, Manisha; Sharma, Amita; Agrawal, Alpana; Gupta, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: It is now well established that not only overt but subclinical thyroid dysfunction can also have adverse effects on fetal and maternal outcomes. In recent years several studies show a much larger prevalence of SCH and marked variation between different ethnic groups. The aim of this study was to find out the prevalence of subclinical hypothyroidism during first trimester in a teaching hospital in North India. Methods: A prospective observational study was conducted in all the consecutive first trimester pregnant women attending Santosh Medical College, Hospital, Ghaziabad from June 2014 to April 2015 after institutional ethics approval and consent from the study subjects. Morning samples of serum were tested for TSH. If serum TSH value was more than 2.5mIU/L then Free T4 and TPO Antibody level were estimated. Results: Serum TSH level was normal in 66.2 % women, 32.5 % women had subclinical hypothyroidism and 1.3 % women had overt hypothyroidism using a first trimester normal reference range of 0.1 to 2.5 mU/l suggested by American Thyroid Association or by the American Endocrine Society. Using 5 mIU/L as upper limit of TSH suggested by some Indian studies serum TSH level was normal in 90.6 % women, 8.1 % women had subclinical hypothyroidism and 1.3 % women had overt hypothyroidism. Conclusion: The prevalence of SCH is very high in our study population. We feel that the use of thyroid function reference values based on studies using different populations and different backgrounds can introduce bias in the evaluation of a local population.